A spatially periodic flow and heat transfer in a rectangular channel with one ribbed wall - Ris Vladimir; Galaev Sergey; Levchenya Alexander (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
The systematic data on the effect of ribbing on the parameters of a relative (in comparison with a smooth channel) increase in hydraulic resistance p and heat transfer q in the range of Reynolds numbers from 50 to 8106 has been obtained by numerical modeling of a developed spatially periodic flow and stabilized heat transfer of incompressible gas with a Prandtl number of 0.7 in a rectangular channel with one-sided internal ribbing. In the laminar regime, the q value was found to be small and amounted about 10 %, and p value exceeding 2.5. In the turbulent regime, the q value behaved nonmonotonic depending on the Reynolds number, the range of its variation was 1.5–2.6, while p increased from 3.5 to 7.0.